2012
DOI: 10.1016/j.neuroimage.2011.08.102
|View full text |Cite
|
Sign up to set email alerts
|

Impact of state anxiety on the interaction between threat monitoring and cognition

Abstract: How does threat processing impact cognitive performance? To investigate this question, in the present functional magnetic resonance imaging study, participants performed a response-conflict task (neutral, congruent, and incongruent trials) that followed a variable-length shock anticipation period or a corresponding delay during which they would not be shocked. The delay period was cued by a geometric-shaped stimulus indicating whether the subject was in the safe (no shock) or threat (potential shock) condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
114
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(130 citation statements)
references
References 58 publications
(83 reference statements)
13
114
3
Order By: Relevance
“…The behavioral finding that patients’ correct response rate was equal to controls may reflect this lack of difference in PFC or ACC activity. State anxiety impacts the interaction between emotion and cognition via the anterior insula (Choi, Padmala, & Pessoa, 2012), but an abnormal response in this region was not observed in our patients. Instead, patients showed reduced activity in the bilateral angular gyri and right fusiform gyrus while performing the emotional Simon task.…”
Section: Discussioncontrasting
confidence: 62%
“…The behavioral finding that patients’ correct response rate was equal to controls may reflect this lack of difference in PFC or ACC activity. State anxiety impacts the interaction between emotion and cognition via the anterior insula (Choi, Padmala, & Pessoa, 2012), but an abnormal response in this region was not observed in our patients. Instead, patients showed reduced activity in the bilateral angular gyri and right fusiform gyrus while performing the emotional Simon task.…”
Section: Discussioncontrasting
confidence: 62%
“…The previously described study (Alvarez et al, 2011) confirmed that long-duration contexts can engage the BNST; however, two other studies have shown BNST activity in response to much shorter anticipation periods. Choi et al (2012) found elevated BNST activity and skin conductance response during a short 1.75-5.75 s threat context. In another study, Klumpers et al (2014) found greater BNST activity to threat (relative to safe cues) using a 4-s shock anticipation period.…”
Section: Neuropsychopharmacology Reviewsmentioning
confidence: 84%
“…However, based on existing dissociations in the literature (e.g., peripheral distractor processing seems to be either decreased or increased under stress depending on situational factors, see Choi et al, 2012 andSchmitz et al, 2009), we predicted that the two types of strains (physical vs. psychosocial) would have dissociable effects on attention control at the electrophysiological level. Hypervigilance and reduced goal-directed processing were hypothesized to be related to the threat of bodily harm, selectively (Choi et al, 2012;Moser et al, 2005;Shackman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike bodily harm, these psychosocial strains have been suggested to narrow the attentional scope, resulting in decreased early visual responses to irrelevant sensory information (Easterbrook, 1959;Rossi and Pourtois 2012a;Schmitz et al, 2009), without systematically affecting goal-directed behavior. By comparison, sustained anxiety related to the anticipation of uncontrollable physical harm seems mainly to impair attentional control functions, in favor of a bottom-up (ventral) attentional system, which might mediate hypervigilance (thus, enhanced responses to task-irrelevant, but potentially threatening information, see also Bishop et al, 2004;Choi et al, 2012;Cornwell et al, 2011;Pourtois et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation